Inside money, investment, and unconventional monetary policy - Lukas Altermatt (University of Zurich, Department of Economics, 2018)
I develop a new monetarist model to analyze why an economy can fall into a liquidity trap, and what the effects of unconventional monetary policy measures such as helicopter money and negative interest rates are under these circumstances. I find that liquidity traps can be caused by a decrease in the bonds-to-money ratio, by a decrease in productivity of capital, or by an increase in demand for consumption. The model shows that, while conventional monetary policy cannot control inflation in a liquidity trap, unconventional monetary policies allow the monetary authority to regain control over the inflation rate, and that an increase in the bonds-to-money ratio is the only welfare-improving policy.
Keywords: E43; E52; E63; G21; H63; 330; New monetarism; liquidity trap; helicopter money; negative interest rates; government debt; Ricardian equivalence; banking